2004
DOI: 10.1051/0004-6361:20034477
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray review of MS 1054–0321: Hot or not?

Abstract: Abstract. XMM-Newton observations are presented for the z = 0.83 cluster of galaxies MS 1054−0321, the highest redshift cluster in the Einstein Extended Medium Sensitivity Survey (EMSS). The temperature inferred by the XMM-Newton data, T = 7.2 +0.7 −0.6 keV, is much lower than the temperature previously reported from ASCA data, T = 12.3 Donahue et al. 1998), and a little lower than the Chandra temperature, T = 10.4 +1.7 −1.5 keV, determined by Jeltema et al. 2001. The discrepancy between the newly derived temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
38
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 36 publications
(77 reference statements)
11
38
1
Order By: Relevance
“…An investigation of the temperature structure of MS 1054-0321 using XMM-Newton (Gioia et al 2004) indicated a temperature for the whole cluster of 7.2 +0.7 −0.6 keV, lower than any of the temperatures reported previously. The two significant clumps already seen by the ROSAT and the Chandra satellites were also seen in the XMM-Newton data.…”
Section: Cluster Ms 1054-0321contrasting
confidence: 56%
“…An investigation of the temperature structure of MS 1054-0321 using XMM-Newton (Gioia et al 2004) indicated a temperature for the whole cluster of 7.2 +0.7 −0.6 keV, lower than any of the temperatures reported previously. The two significant clumps already seen by the ROSAT and the Chandra satellites were also seen in the XMM-Newton data.…”
Section: Cluster Ms 1054-0321contrasting
confidence: 56%
“…MS 1054-0321 (Gioia et al 2004): the XMM-Newton observations yield temperature, redshift (through observation of the iron line in the X-ray spectrum) and flux estimates of T = 7.2 +0.7 −0.6 keV, z = 0.847 +0.057 −0.040 and f X [0.5,2] keV = (1.9±0.09)×10 −13 erg/s/cm 2 , respectively; and they also provide a detailed image showing several components to the cluster's structure. The effective exposure time needed was ∼25 ks.…”
Section: Xmm-newton Follow-up Of the New Planck Clustersmentioning
confidence: 99%
“…MS 1054À03, the most X-ray-luminous cluster in the Einstein Extended Medium Sensitivity Survey (Gioia et al 1990;Gioia & Luppino 1994), has also been the target of numerous X-ray studies and has a similarly complex morphology (Donahue et al 1998;Jeltema et al 2001), although in its case the merger is more advanced and the total mass is roughly twice that of RX J0152.7À1357. While estimates of the temperature of MS 1054À03 have varied widely (see Gioia et al 2004 for an X-ray review of this cluster), the most recent determination using the latest Chandra calibration gives 8:9 þ1:0 À0:8 keV (Jee et al 2005b). Its mean redshift is z ¼ 0:831 based on $150 members (van Dokkum et al 2000; K.-V. Tran et al 2006, in preparation).…”
Section: Introductionmentioning
confidence: 99%